An investigation on the graphitic carbon nitride reinforced polyimide composite and evaluation of its tribological properties. Issue 41 (23rd June 2017) - Zhu, Lin; You, Liangjun; Shi, Zhaoxin; Song, Haojie; Li, Songjun
ABSTRACT: This article presented a novel application for the graphitic carbon nitride (g‐C3 N4 ), which was used as nanofillers to improve the tribological properties of polyimide (PI). The composite based on PI and g‐C3 N4 was prepared by mechanical mixing process and hot compression molding process. The characterizations of g‐C3 N4 and PI/g‐C3 N4 composites were investigated by Fourier transform infrared spectroscopy, X‐ray diffraction, thermogravimetric analysis, and scanning electron microscopy. Friction and wear tests were carried out using UMT‐2 reciprocating tribo‐tester against stainless steel ball under dry friction. The results showed that the amount of g‐C3 N4 was decisive to the tribological properties of PI/g‐C3 N4 composites. The optimal tribological properties occurred when the amount of g‐C3 N4 was 10 wt %, which showed the smallest friction coefficient and the lowest wear rate. Furthermore, this work provided an example of application for the g‐C3 N4 as the excellent nanofiller in polymer matrix composites. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45403. Abstract :